2023
DOI: 10.1186/s12916-023-02975-8
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in gut microbiota composition in patients with polycystic ovary syndrome: a systematic review and meta-analysis

Abstract: Background The results of human observational studies on the correlation between gut microbiota perturbations and polycystic ovary syndrome (PCOS) have been contradictory. This study aimed to perform the first systematic review and meta-analysis to evaluate the specificity of the gut microbiota in PCOS patients compared to healthy women. Methods Literature through May 22, 2023, was searched on PubMed, Web of Science, Medline, Embase, Cochrane Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…30 A recent study demonstrated that several SCFAproducing bacteria decreased significantly in patients with PCOS, including Butyricimonas, Blautia, Coprococcus, and F. prausnitzii. 31 These bacteria are regarded as SCFA producers and have beneficial effects on hosts. F. prausnitzii exhibits anti-inflammatory activity and maintains mucosal immune homeostasis.…”
Section: The Content Of Scfa Affects Insulin Resistance Occurrencementioning
confidence: 99%
See 1 more Smart Citation
“…30 A recent study demonstrated that several SCFAproducing bacteria decreased significantly in patients with PCOS, including Butyricimonas, Blautia, Coprococcus, and F. prausnitzii. 31 These bacteria are regarded as SCFA producers and have beneficial effects on hosts. F. prausnitzii exhibits anti-inflammatory activity and maintains mucosal immune homeostasis.…”
Section: The Content Of Scfa Affects Insulin Resistance Occurrencementioning
confidence: 99%
“…prausnitzii . 31 These bacteria are regarded as SCFA producers and have beneficial effects on hosts. F .…”
Section: The Role Of Gut Microbiota In the Pathogenesis Of ...mentioning
confidence: 99%
“…The contribution of the microbiota in the development and course of various gynecological diseases was studied by a number of scientists [14,[48][49][50]. Nowadays a great attention is to the meaning of vaginal and gut microbiota in PCOS course [51,52]. Gut microbiota influences of the development and course of PCOS and other diseases that can be associated with coronary pathology, obesity, T2DM.…”
Section: г і н е к о л о г і яmentioning
confidence: 99%
“…The researches showed that there is gut dysbiosis in PCOS patients, "which might be characterized by the reduction of short-chain fatty acid-producing and bile-acidmetabolizing bacteria, suggests a shift in balance to favor pro-inflammatory rather than anti-inflammatory bacteria" [51]. P. J. Torres et al found that low α diversity by PCOS which was negatively correlated with hyperandrogenism, total testosterone and hirsutism [61].…”
Section: г і н е к о л о г і яmentioning
confidence: 99%
“…Thus, alpha diversity measures the diversity of a particular population within the sample, while beta diversity measures are estimates of similarity between samples [18,19]. A systematic review in adult women with PCOS has demonstrated a significant alteration of the gut microbiota [20].…”
Section: Introductionmentioning
confidence: 99%